Vertical aligned solid‐state electrolyte templated by nanostructured "upright" cellulose film layers for advanced cell performance. Issue 4 (18th December 2022) - Zhang, Hao; An, Xingye; Yang, Yiluo; Long, Yinying; Nie, Shuangxi; Liu, Liqin; Yang, Guihua; Tian, Zhongjian; Cao, Haibing; Cheng, Zhengbai; Liu, Hongbin; Ni, Yonghao
Abstract: In this work, an "upright" cellulose layered template, which can be precisely controlled by the fiber orientation and thickness of anisotropic cellulose film, was first developed to prepare vertically aligned Li7 La3 Zr2 O12 (LLZO) ceramic membrane with low tortuosity and uniform porosity. The flexible composite solid‐state electrolytes (CSEs) were synthesized by incorporating poly(ethylene oxide) (PEO) polymer into LLZO architecture, and exhibited distinguished mechanical strength, elevated ionic conductivity (2.1 × 10 −4 S cm −1 ) and excellent interface compatibility with lithium anodes. The assembled LiFePO4 /lithium full cells assembled with as‐obtained CSEs can reach large discharge capacities of 172.3 mAh g −1 with coulombic efficiencies of above 99% and capacity retention of 93.1% even after 200 cycles. These results clearly demonstrate that the sophisticated design of vertical aligned cellulose layered template with fine‐scale size and exquisite architecture is a promising and practical approach in fabricating flexible LLZO@PEO‐LiTFSI CSEs with high‐safety and high‐performance. Abstract : A nanostructured vertically aligned LLZO ceramic membrane and multiscale aligned LLZO@PEO‐LiTFSI CSE via an "upright" cellulose layer was well designed.